2018
DOI: 10.1021/acs.jpcc.7b11609
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctionalities of an Azine-Linked Covalent Organic Framework: From Nanoelectronics to Nitroexplosive Detection and Conductance Switching

Abstract: By using the state-of-the-art theoretical method, we have investigated the electronic structures of recently synthesized two-dimensional azine-linked covalent organic framework (ACOF-1). Our result indicates that ACOF-1 is a direct band gap semiconductor, suggesting useful application in nanoelectronics. Its one-dimensional (1D) structure also exhibits semiconducting properties. Furthermore, this azine-linked COF is found to be practically useful for selective sensing of nitroaromatics over nitroaliphatics. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“…Experimentally, the assembling of nitrogen-containing linkages and benzene-based nodes into 2D frameworks is possibly realized via dihydration reaction for some 2D COFs, as illustrated in Figure S7. Note that many imine-linked and azine-linked , COFs have been reported experimentally with dehydrogenation reactions. Note that for azo-linked COFs, it is difficult to synthesize the 2D structure due to some competing reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, the assembling of nitrogen-containing linkages and benzene-based nodes into 2D frameworks is possibly realized via dihydration reaction for some 2D COFs, as illustrated in Figure S7. Note that many imine-linked and azine-linked , COFs have been reported experimentally with dehydrogenation reactions. Note that for azo-linked COFs, it is difficult to synthesize the 2D structure due to some competing reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Though the calculated formation energies have a wide range from −3.84 to 0.34 eV, some of the them have been experimentally synthesized in previous studies. To our knowledge, I-TA, I-TST, Ai-BZ, Ai-TBZ, and Ai-TST have been experimentally realized, named as TPA, TTI-COF, ACOF-1, , N0-COF, and N3-COF, respectively. Table S1 summarizes the comparison of our calculated results with some synthesized 2D nitrogen-linked COFs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, those studies indicated the interferences along π-electrons are the main driving forces for the host-guest interactions in case of such electron-rich, conjugated host-guests [44,45]. The quench of photoluminescence after nitrobenzene (electron acceptor) exposure during the optical sensing applications can be a good experimental proof for this behavior [33,[46][47][48][49].…”
Section: Techniques For Covalent Organic Framework Film Formationmentioning
confidence: 93%
“…Moreover, those studies indicated the interferences along -electrons are the main driving forces for the host-guest interactions in case of such electron-rich, conjugated host-guests [44,45]. The quench of photoluminescence after nitrobenzene (electron acceptor) exposure during the optical sensing applications can be a good experimental proof for this behavior [33,[46][47][48][49]. Since porous organic polymers have a non-soluble nature (except some PIMs) due to their highly rigid, branched, long-alkyl-free backbone, forming uniform films from those compounds has been a challenge for their integration to devices, hence their limited utilization for electronic applications [50].…”
Section: Techniques For Covalent Organic Framework Film Formationmentioning
confidence: 93%
See 1 more Smart Citation